Development of Highly Bendable Transparent Window Electrodes Based on MoOx, SnO2, and Au Dielectric/Metal/Dielectric Stacks: Application to Indium Tin Oxide (ITO)-Free Perovskite Solar Cells - Lucarelli, Giulia; Brown, Thomas M. (Frontiers in Materials, 2019)
Indium-doped tin oxide (ITO) is the transparent conductive material of choice for a wide range of optoelectronic devices such as sensors, light-emitting diodes and solar cells. However, its brittle nature, high cost, scarcity as well as aggressive deposition via sputtering determine the need to find cheap alternatives with high optical transparency, low sheet resistance, and mechanical flexibility. Dielectric/metal/dielectric (D/M/D) electrodes fulfill all these requirements and are deposited via low embodied energy low-temperature processing. We developed D/M/D multilayered electrodes based on thermally evaporated MoOx or solution-processed SnO2 seed layers, a thermally evaporated ultrathin Au film, and a spin-coated SnO2 top layer on rigid glass substrates. We first systematically unraveled the role of each layer on the resistance-transmittance properties of the full D/M/D electrode structure. By optimizing the thickness of the seed, metal and the top layer, we obtained electrodes with transmittance of 72% at 550 nm and a minimum sheet resistance of 9  sq-1. Subsequently, these optimized multilayered stacks were employed as bottom electrodes for perovskite solar cells with glass/D/M/D/mesoporous-TiO2/CH3NH3PbI3/spiro-MeOTAD/Au device architecture, delivering power conversion efficiencies (PCE) of 10.7%. Further, we deposited and characterized D/M/D electrodes on flexible polyethylene terephthalate (PET) films, achieving a maximum PCE of 7.6%. The difference in performance compared to rigid glass devices can be ascribed to the different wetting of the active layer on PET substrates. Flexible D/M/D electrodes displayed excellent mechanical properties compared to commercial PET/ITO, showing completely stable sheet resistance after repeated bending even down to 1.5 mm of curvature radius, whereas PET/ITO showed one order of magnitude increase in sheet resistance in the same mechanical test, due to formation of cracks in the conductive oxide. Our optimized D/M/D stacks on glass and especially on PET or other flexible substrates are therefore excellent alternatives to ITO as transparent window electrodes for low-cost, light-weight and conformal optoelectronics applications.